A small heat shock protein Fmp28 influences virulence by regulating Als3 expression via the cAMP-PKA signaling pathway in Candida albicans - Junjun Tan; Qiong Liu; Zhiping Liu; Yanli Cao; Xiaomin Yu; Qianjun Zhao; Niya Hu; Yanling Liu; Yuwei Wan; Yeming Zhang; Huizhen Tian; Lingbing Zeng; et al. (mBio)
ABSTRACT Small heat shock proteins are evolutionarily conserved molecular chaperones with diverse cellular roles. However, our understanding of their functions in pathogenic microorganisms remains limited. In this study, we identified and characterized Fmp28, a novel small heat shock protein that enhances virulence in Candida albicans, and explored its regulatory mechanism. The expression of Fmp28 was significantly upregulated at both transcriptional and translational levels when C. albicans was subjected to physiological temperature (37°C), osmotic stress, or cell wall stress. Deletion of Fmp28 significantly impaired growth, adhesion, biofilm formation, invasive growth, and virulence at physiological temperature (37°C), respectively. Transcriptome analysis identified Als3 as a key downstream target of Fmp28. Notably, Als3 overexpression substantially rescued the impairments in adhesion, biofilm formation, invasion, and virulence caused by FMP28 deletion. Deletion of FMP28 also led to downregulated expression of genes in the cAMP-PKA pathway, as well as reduced intracellular ATP and cAMP levels. By adding exogenous cAMP analogs, the adhesion and biofilm formation in the fmp28Δ/Δ mutant could be partially restored. In conclusion, the findings in this study demonstrated that Fmp28 maintained C. albicans virulence at physiological temperature by regulating Als3 expression through the cAMP-PKA signaling pathway, establishing Fmp28 as a potential therapeutic target for treating C. albicans infections.IMPORTANCEWe have identified Fmp28 as a novel small heat shock protein that is essential for C. albicans adaptation to diverse stresses and full virulence. Furthermore, we elucidated that Fmp28 interacts with Qcr10 on the mitochondria to maintain the concentration of ATP, promoting virulence by regulating Als3 expression via the cAMP-PKA pathway, providing new insights into how C. albicans maintains its stress adaptation and full virulence at a physiological temperature of 37°C. Our findings established Fmp28 as a potential therapeutic target for treating C. albicans infections, which is particularly relevant, given the rising concern about antifungal resistance.